A Correlation between Avalanches and Teleconnection Indices in the Italian Alps - Bee, C.; Zugliani, D.; Rosatti, G. (Montana State University Library, 2024)
Teleconnections, such as the North Atlantic Oscillation (NAO) and the Arctic Oscillation (AO), play significant roles in wintertime weather patterns across wide regions of the Northern Hemisphere, including Western Europe and the Mediterranean basin. In the literature, avalanche activity has been related to major teleconnection indices in various European mountain regions and some Pacific coastal ranges in North and South America. However, no studies have been conducted on the Italian Alps, and this work aims to investigate the possible correlations among teleconnection indices that influence avalanches on the southern portion of the Alps. As the Alpine region sits at a crossroads of Atlantic and Mediterranean influences, this study includes the Western Mediterranean Oscillation (WeMO) alongside the NAO and AO teleconnection indices. Avalanche time series data collected in two Italian Alpine regions and historical data of teleconnection indices were used to investigate possible correlations between the number of avalanche days in each winter season and the values of the seasonal teleconnection indices. The analysis considers avalanche days instead of single events to reduce errors due to non-recorded avalanches, especially during extended periods of bad weather. Spearman correlation coefficient (R) was utilized to assess the relationship between time series data of variables, offering information on the strength and direction of the association. Results reveal different behaviors of the dataset from the western sector of the Alps compared to the eastern one. While the NAO and AO show little correlation with the data in the western Italian Alps, confirming previous findings in the French Alps, they are significantly anticorrelated with the data in the eastern Italian Alps. The WeMO has the most significant influence on avalanches in the western Italian regions. This research could potentially provide avalanche forecasters with meaningful information on seasonal avalanche tendencies, especially as the ...